2023
DOI: 10.3390/microorganisms11122880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Oxide and Copper Sulfate on Antibiotic Resistance Plasmid Transfer in Escherichia coli

Otávio Hallal Ferreira Raro,
Laurent Poirel,
Patrice Nordmann

Abstract: Heavy metals such as zinc (Zn) and copper (Cu) may be associated with antibiotic resistance dissemination. Our aim was to investigate whether sub-lethal dosage of Zn and Cu may enhance plasmid transfer and subsequently resistance genes dissemination. Plasmid conjugation frequencies (PCF) were performed with Escherichia coli strains bearing IncL-blaOXA-48, IncA/C-blaCMY-2, IncI1-blaCTX-M-1, IncF-blaCTX-M-1, and IncX3-blaNDM-5 as donors. Mating-out assays were performed with sub-dosages of zinc oxide (ZnO) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Zn oxides protect LexA from cleavage by interfering with RecA [52]. Copper also influences the overall SOS response [53]. Following a 20 s irradiation, 177 genes were found to be differentially transcribed in the range of logFC −2.2 to 1.9 (Figure 3B, Table 3).…”
Section: Transcriptome Analyses Of High-power Blue Laser Radiation Tr...mentioning
confidence: 99%
“…Zn oxides protect LexA from cleavage by interfering with RecA [52]. Copper also influences the overall SOS response [53]. Following a 20 s irradiation, 177 genes were found to be differentially transcribed in the range of logFC −2.2 to 1.9 (Figure 3B, Table 3).…”
Section: Transcriptome Analyses Of High-power Blue Laser Radiation Tr...mentioning
confidence: 99%
“…Indeed, recent investigations showed that ZnO treatment of postweaning pigs can favour the selection and development of antimicrobial-resistant (AMR) and multidrug-resistant (MDR) E. coli [15]. Furthermore, bacterial in vitro studies gave evidence that stress conditions such as heavy metals exposure may play an important role in potentially inducing acquisition of antibiotic resistance genes through horizontal gene transfer [16,17]. To address these concerns, it is crucial to explore more sustainable and safe alternatives for treating gastrointestinal issues in animals, including better livestock management, judicious antibiotic use, and the use of natural alternatives like probiotics, prebiotics, and plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent investigations showed that ZnO treatment of post-weaning pigs can favour the selection and development of antimicrobial-resistant (AMR) and multidrug-resistant (MDR) E. coli [ 15 ]. Furthermore, bacterial in vitro studies provided evidence that stress conditions such as heavy metals exposure may play an important role in potentially inducing acquisition of antibiotic resistance genes through horizontal gene transfer [ 16 , 17 ]. To address these concerns, it is crucial to explore more sustainable and safe alternatives for treating gastrointestinal issues in animals, including better livestock management, judicious antibiotic use, and the use of natural alternatives like probiotics, prebiotics, and plant extracts.…”
Section: Introductionmentioning
confidence: 99%